The Effect of Dietary Fats and Antioxidants on Fatty Acid Composition and Fertility Ability of Fowl Semen - Muzaffer Çördük (Journal of Agricultural Sciences)
The typical fatty acid profile of the spermatozoa of domesticated poultry is characterized by the predominance of C20-22: n-6 polyunsaturated. The fish oil diet induced a significant but limited increase in the proportion C22:6n-3 in spermatozoa phospholipids in parallel with an equivalent decrease in the proportion of C20:4n-6 and C22:4n-6. In addition, the fish oil diet gave significantly higher sperm fertility rate than vegetable oil diet, but fatty acid profile of spermatozoa display a considerable degree of resistance to manipulation by dietary means. These results clearly show that the lipid composition of diet may modify the fatty acid composition of semen and fertilizing ability. Antioxidants have protected sperm membranes against toxic reactive oxygen species, thereby extending the life span of sperm